2016
DOI: 10.4172/2165-7386.1000260
|View full text |Cite
|
Sign up to set email alerts
|

How We should Support Patients’ Decision Making at End of Life – From a National Survey of Hospital Ethics Committees in Japan

Abstract: Objective: To overview frequent ethical issues arising in clinical setting and the role of hospital ethics committees (HECs) from a national survey in Japan.Design: Cross sectional survey using questionnaire by post to 4,911 randomly selected hospitals throughout Japan.Results: Among 1,555 hospitals responding to the survey, the most frequent ethical issue likely to arise in practice was end-of-life care (n = 1,022). A total of 787 hospitals (51.1%) reported that they already had an ethics committee in place a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A recent study on 4000 hospitals in Japan reported 51.1% of the surveyed hospitals to have an ethics committee. Moreover, 16.8% of the hospitals were working on developing their HECs (51). Korea When faced with ethical dilemmas in university hospitals, residents and physicians in Korea have very limited access to clinical ethicists or active hospital ethics committees to consult with (52).…”
Section: Western Pacific Region Australiamentioning
confidence: 99%
“…A recent study on 4000 hospitals in Japan reported 51.1% of the surveyed hospitals to have an ethics committee. Moreover, 16.8% of the hospitals were working on developing their HECs (51). Korea When faced with ethical dilemmas in university hospitals, residents and physicians in Korea have very limited access to clinical ethicists or active hospital ethics committees to consult with (52).…”
Section: Western Pacific Region Australiamentioning
confidence: 99%